Californian Wildfire Smoke Over Europe: A First Example of the Aerosol Observing Capabilities of Aeolus Compared to Ground‐Based Lidar - Baars, Holger; Radenz, Martin; Floutsi, Athena Augusta; Engelmann, Ronny; Althausen, Dietrich; Heese, Birgit; Ansmann, Albert; Flament, Thomas; Dabas, Alain; Trapon, Dimitri; Reitebuch, Oliver; Bley, Sebastian; et al. (Geophysical research letters, 2021)
In September 2020, extremely strong wildfires in the western United States of America (i.e., mainly in California) produced large amounts of smoke, which was lifted into the free troposphere. These biomass‐burning‐aerosol (BBA) layers were transported from the US west coast toward central Europe within 3–4 days turning the sky milky and receiving high media attention. The present study characterizes this pronounced smoke plume above Leipzig, Germany, using a ground‐based multiwavelength‐Raman‐polarization lidar and the aerosol/cloud product of ESA’s wind lidar mission Aeolus. An exceptional high smoke‐AOT >0.4 was measured, yielding to a mean mass concentration of 8 μg m−3. The 355 nm lidar ratio was moderate at around 40–50 sr. The Aeolus‐derived backscatter, extinction and lidar ratio profiles agree well with the observations of the ground‐based lidar PollyXT considering the fact that Aeolus’ aerosol and cloud products are still preliminary and subject to ongoing algorithm improvements. Plain Language Summary In September 2020, extremely strong wildfires in the western USA (i.e., mainly in California) produced large amounts of smoke. These biomass burning aerosol (BBA) layers were transported from the US west coast towards central Europe within 3‐4 days. This smoke plume was observed above Leipzig, Germany, for several days turning the sky milky and receiving high media attention ‐ it was the highest perturbation of the troposphere in terms of AOT ever observed over Leipzig. The first smoke plume arrived on 11 September 2020, just in time for a regular overpass of the Aeolus satellite of the European Space Agency (ESA). Aeolus accommodates the first instrument in space that actively measures profiles of a horizontal wind component in the troposphere and lower stratosphere. Aeolus has been launched to improve weather forecasts while assimilating the Aeolus wind profile data in near–real time. But Aeolus also delivers profiles of aerosol and cloud optical properties as spin‐off products. We performed a first assessment of the aerosol profiling capabilities of Aeolus while precisely analyzing the smoke plume above Leipzig with a ground‐based multiwavelength‐Raman‐polarization lidar. But we also show the dramatic impact of fires in the western USA on atmospheric conditions over central Europe. Key Points Smoke from the extraordinary 2020 Californian wild fires traveled within 3–4 days toward Europe Highest Aerosol Optical Thickness ever measured in the free troposphere over Leipzig, Germany, Central Europe, with ground‐based lidar Unique opportunity for a first assessment of the aerosol optical profiles of the spaceborne wind lidar mission Aeolus